Práticas de autonomia e agência na escola pública: reflexões sobre a incorporação de inovações no ensino de língua inglesa - Marchi, Amabile Leite (2016)
This research aims to bring reflections on the autonomy and agency in the process of language learning in Brazilian public schools. Therefore, we did a reading focused on Brazilian official documents in order to understand its guidelines about the research topic. Then, we conceptualize the terms mentioned above - autonomy and agency - using as theoretical researchers from the area of education of foreign languages and education, as Clarissa Menezes Jordão and Vera Lúcia Menezes de Oliveira Paiva. Later, we consider other pedagogical practices that have in essence the promotion of individual autonomy, as Waldorf Education, Escola da Ponte and Escola Projeto Âncora. For this, we look back on authors such as Jonas Bach Junior, José Pacheco among others. Finally, we made an analysis of some points that can benefit public schools based on these other ways of looking at education. From the foregoing, we propose that we may use some strategies so that English language classes in public schools are better taken advantage of and make more sense to the live of the students.